Anti-Violence Village Movement: Empowering Women and Children to Reduce the Rate of Domestic Violence in Jambenenggang Village - Mulyanti, Asti Sri; Purwanti, Dian; Mulyadi, Andi; Pramudita, Roni Renaldi; Afrisilia, Abel; Fawwaz, Salma Talitha (Faculty of Law, Universitas Pattimura, 2026)
Introduction: Domestic violence in Jambenenggang Village is a serious issue involving not only physical violence, but also verbal and non-verbal violence, which has a significant impact on housewives, children, and women. The main causative factors include fear and embarrassment among victims that prevent them from reporting, which is exacerbated by unfavorable economic conditions.Purposes of The Devotion: This service aims to create effective interventions to break the cycle of domestic violence.Method of The Devotion: The methods used include socialization, training, technology application, and continuous mentoring.Results Main Findings of the Devotion: The results of the service show that increased access to the law and the creation of a safe place to complain make victims of violence feel more empowered to report.